Is Work Life Balance Matter in Accounting Profession? - Putuhena, Hempry; Fauzan S, M Rifkhi; Zalni; Kriswantini, Dwi (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2025)
This study investigates the impact of work involvement, work engagement, and work satisfaction on work-life balance within the accounting profession. Additionally, it proposes strategies to support employees in achieving a healthy balance and identifies key factors contributing to workplace changes that influence work-life balance. The relationships between the independent and dependent variables were analyzed using SPSS, based on a sample of 54 accounting professionals with diverse work experiences. The findings reveal that work involvement and work engagement have a positive effect on work-life balance, whereas work satisfaction does not exhibit a significant impact. Hypothesis testing results confirm that only the first two hypotheses were supported, while the third was rejected. The novelty of this study lies in its focus on work-life balance within the accounting profession, a field characterized by high workloads and stringent accuracy demands.